The Investment Climate and the Firm : Firm-Level Evidence from China - Hallward-Driemeier, Mary; Wallsten, Scott; Xu, Lixin Colin (World Bank, Washington, DC, 2014)
The importance of a country's "investment climate" for economic growth has recently received much attention. The authors address the general lack of appropriate data for measuring the investment climate and its effects. The authors use a new survey of 1,500 Chinese enterprises in five cities to more precisely define and measure components of the investment climate, highlight the importance of firm-level data for rigorous analysis of the investment climate, and investigate empirically the effects of this comprehensive set of measures on firm performance in China. Overall, their firm-level analysis reveals that the main determinants of firm performance in China are international integration, entry and exit, labor market issues, technology use, and access to external finance.